PROSES MANUFAKTUR ALAT PENGASAPAN IKAN MODEL TABUNG DENGAN ROTATING GRILL STAINLESS STEEL - Ilham Rizki Alhasybi, (2022)
Fish catches or cultivation experience faster decay after being landed, so it is necessary to be appropriate processing so that fish can be stored longer by fogging fish smoking is one way of processing fish that can slow down the growth of spoilage microorganisms, So that fish have longer resistance. The fumigation method using a closed system is considered more efficient because the smoke produced from coconut or wood shells can be isolated, creating more smoke. Fumigation in fish will be more leverage. This study aims to manufacture fish fogging devices with a grill that can be rotated 180 degrees and know what processes are carried out in the process of making tools and the total costs of making fish fogging devices. The results obtained are based on the calculation and trial of the tool, obtained the total time of machinery needed for 509.46 minutes or 8.4 hours with a total operational cost of Rp. 2,513,372,33. The tools that have been made can take as much as 8 kg of fish or 21 fish every one time, the smoking time is required +- 5 hours and consumes 15 kg of coconut shell, and obtained a fogging capacity of 0.9 kg/hour, with a ratio of fish mass shrinkage (yield) of 56.25%.